Revitalizing Gen-Z Christians in Indonesia towards a realistic, pluralistic, and activist spirituality based on the theory of Thomas à Kempis - Hasiholan, Anggi Maringan (Institut Agama Kristen Negeri Toraja, 2024)
Generation Z of Indonesian Christians, who are full of knowledge and technology, tend to ignore their identity as followers of Jesus. Anarchic, destructive, and immoral behavior has become a regular trend among Generation Z Christians. In order to address this problem, relevant teaching approaches and sources are needed. The approach offered is teaching-encountering-based discipleship and teaching sources through reincarnating the thoughts and spirituality of Thomas à Kempis as Devotio Moderna. The Kempis trilogy's offering, namely the opposition pairs in the fabric of today's reality, God's sovereignty, and the obedience of God's people, need to be echoed for Generation Z. This research aims to extract the spirit of Thomas à Kempis for the life of Generation Z of Indonesian Christians. The method used is historical research, the primary source of which is the book De Imitatione Christi by Thomas à Kempis. The results of the study show that Generation Z of Indonesian Christians can vitalize a realistic, pluralistic, and Activist spirituality if (i) they understand the essence and purpose of life, (ii) realizing that there is a confusion of values and culture; (iii) wise and critical in accepting new information and lifestyles; (iv) dare to speak out on sensitive issues that occur in the general public and the Church.